2018
DOI: 10.21314/jrmv.2018.182
|View full text |Cite
|
Sign up to set email alerts
|

A central limit theorem formulation for empirical bootstrap value-at-risk

Abstract: In this paper, the importance of the empirical bootstrap (EB) in assessing minimal operational risk capital is discussed, and an alternative way of estimating minimal operational risk capital using a central limit theorem (CLT) formulation is presented. The results compare favorably with risk capital obtained by fitting appropriate distributions to the same data. The CLT formulation is significant in validation because it provides an alternative approach to the calculation that is independent of both the empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We attempt to predict the future lossesx t using time series derived from historic data. In [33], we found that predicting 3 months into the future was sufficiently accurate in most cases. Therefore, suppose that n quarters t 1 , t 2 , ..., t n are available and that "windows" of r consecutive quarters are taken.…”
Section: Forward Stress Framework: Operationmentioning
confidence: 85%
“…We attempt to predict the future lossesx t using time series derived from historic data. In [33], we found that predicting 3 months into the future was sufficiently accurate in most cases. Therefore, suppose that n quarters t 1 , t 2 , ..., t n are available and that "windows" of r consecutive quarters are taken.…”
Section: Forward Stress Framework: Operationmentioning
confidence: 85%
“…The Bühlmann-Straub method is described in Bühlmann and Gisler (2005). It is reiterated in a simpler form in Mitic and Bloxham (2018), where the two methods of calculating variance (one is the variance of all the data, the other is the variance of means of segments of the data) are clarified. So, if V int and V ext are the VaRs for an internal and external data set, respectively, the combined VaR, V , is given by…”
Section: Combination Of Internal and External Datamentioning
confidence: 99%